Assessing the amorphousness and periodicity of common domain boundaries in silica bilayers on Ru(0 0 0 1). (15th November 2016) - Burson, Kristen M; Büchner, Christin; Heyde, Markus; Freund, Hans-Joachim
Abstract: Domain boundaries are hypothesized to play a role in the crystalline to amorphous transition. Here we examine domain boundary structures in comparison to crystalline and amorphous structures in bilayer silica grown on Ru(0 0 0 1). Atomically resolved scanning probe microscopy data of boundaries in crystalline bilayer films are analyzed to determine structural motifs. A rich variety of boundary structures including rotational, closed-loop, antiphase, and complex boundaries are identified. Repeating units with ring sizes of 558 and 57 form the two most common domain boundary types. Quantitative metrics are utilized to assess the structural composition and degree of order for the chemically equivalent crystalline, domain boundary, and amorphous structures. It is found that domain boundaries in the crystalline phase show similarities to the amorphous phase in their ring statistics and, in some cases, in terms of the observed ring neighborhoods. However, by assessing order and periodicity, domain boundaries are shown to be distinct from the glassy state. The role of the Ru(0 0 0 1) substrate in influencing grain boundary structure is also discussed.